The Influence Of Local Wisdom And Promotion On The Purchase Decisions Of Culinary Foods By Generation Z In Denai Lama Tourism Village - Larasati Br. Br. Siagian; Adelina Lubis; Ikbar Pratama (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This research aims to determine the "Influence of Local Wisdom and Promotion on the Purchase Decisions of Culinary Foods by Generation Z in Denai Lama Tourism Village" by referring to the variable indicators in this study. This study uses a quantitative research method assisted by the Smart-PLS program in data processing. The research results show that local wisdom on purchasing decisions has an influence of 0.983 with a t-statistics value of 66.514 and a p-value of 0.000 < 0.05. Promotion on purchasing decisions has an influence of 0.005 with a t-statistics value of 0.291 and a p-value of 0.771 > 0.05. Thus, H1 and H2 are accepted.